Efektivitas Media Interaktif Wordwall dan Benda Konkret Bangun Ruang terhadap Motivasi dan Hasil Belajar Matematika - Trisnawati, Nika Fetria; Mafinanik, Ajima; Rumfaan, Alowesia Rosalina; Gobai, Amison; Kambu, Valensia; Sundari, Sundari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to examine the effectiveness of using interactive media such as Wordwall quizzes and concrete objects in improving students' motivation and learning outcomes in mathematics at SMP Negeri 6 Kota Sorong. The research employed a quasi-experimental approach conducted on Friday, July 17, 2025, involving 20 eighth-grade students. The instruments used included a motivation questionnaire, observation sheets, and a post-test on geometry. The findings revealed that Wordwall stimulated students' enthusiasm through engaging visual competition, while concrete models helped students comprehend geometric concepts more concretely. About 80% of students achieved scores above the minimum passing grade, and over 90% reported increased motivation through the questionnaire. Observational data supported the conclusion that students were actively engaged. These findings indicate that Wordwall and concrete models are effective instructional media that improve mathematics learning and offer innovative solutions, particularly for resource-limited schools.